Adsorption – Desorption Behavior of Penoxsulam Herbicide on Soils with Different Characteristics. Issue 1 (2nd January 2021) - Pandey, Vandita; Srivastava, Anjana; Srivastava, Prakash Chandra
ABSTRACT: A safe use of herbicide in the environment can be assessed by it's adsorption – desorption behavior in soil. In the present work laboratory studies were performed to examine adsorption-desorption behavior of penoxsulam herbicide on six soils having widely different properties. Adsorption kinetics of penoxsulam was best accounted by pseudo-first order model. Among acidic soils, soil having the lowest pH (5.36) showed highest partition coefficient (kd ) whereas, in case of alkaline soils, soil of relatively less alkaline pH (7.88) and higher silt and organic content had higher kd value. The kd of penoxulam showed a highly significant and negative correlation with soil pH (r = −0.987, significant at p ≤ 0.01). Adsorption-desorption data fitted well to Freundlich isotherm model. Percent desorption of penoxsulam showed a highly significant and positive correlation with soil pH (r = 0.973, significant at p ≤ 0.01). Step-wise multiple regression analysis revealed that kd, Freundlich adsorption-desorption isotherm constants and hysteresis of penoxulam in soils could be successfully predicted by soil properties. The fourier transformed infrared spectral comparisons showed that adsorption of penoxsulam on soil occurred through H-bonding of several polar moieties with soil constituents besides a likely complex reaction of triazole group with some transition metals present on soil exchange complex.